Pharmacokinetics and Safety of a Raltegravir-Containing Regimen in Children Aged 4 Weeks to 2 Years Living With Human Immunodeficiency Virus and Receiving Rifampin for Tuberculosis. (25th May 2020) - Krogstad, Paul; Samson, Pearl; Acosta, Edward P; Moye, Jack; Townley, Ellen; Bradford, Sarah; Brown, Emily; Denson, Kayla; Graham, Bobbie; Hovind, Laura; Sise, Thucuma; Teppler, Hedy; et al.
Abstract: Pharmacological interactions limit treatment options for children living with human immunodeficiency virus (HIV) and tuberculosis (TB). We found that 12 mg/kg twice daily raltegravir chewable tablets (administered after crushing) safely achieved pharmacokinetic targets in children living with HIV aged 4 weeks to <2 years receiving concurrent rifampin to treat TB. Clinical Trials Registration: NCT01751568.